Adaptation and psychometric properties of the ISPCAN Child Abuse Screening Tool for use in trials (ICAST-Trial) among South African adolescents and their primary caregivers. (August 2018) - Meinck, Franziska; Boyes, Mark E.; Cluver, Lucie; Ward, Catherine L.; Schmidt, Peter; DeStone, Sachin; Dunne, Michael P.
Abstract: Child abuse prevention research has been hampered by a lack of validated multi-dimensional non-proprietary instruments, sensitive enough to measure change in abuse victimization or behavior. This study aimed to adapt the ICAST child abuse self-report measure (parent and child) for use in intervention studies and to investigate the psychometric properties of this substantially modified tool in a South African sample. First, cross-cultural and sensitivity adaptation of the original ICAST tools resulted in two preliminary measures (ICAST-Trial adolescents: 27 items, ICAST-Trial caregivers: 19 items). Second, ICAST-Trial data from a cluster randomized trial of a parenting intervention for families with adolescents (N = 1104, 552 caregiver-adolescent dyads) was analyzed. Confirmatory factor analysis established the hypothesized 6-factor (adolescents) and 4-factor (caregivers) structure. Removal of two items for adolescents and five for caregivers resulted in adequate model fit. Concurrent criterion validity analysis confirmed hypothesized relationships between child abuse and adolescent and caregiver mental health, adolescent behavior, discipline techniques and caregiver childhood abuse history. The resulting ICAST-Trial measures have 25 (adolescent) and 14 (caregiver) items respectively and measure physical, emotional and contact sexual abuse, neglect (both versions), and witnessing intimate partner violence and sexual harassment (adolescent version). The study established that both tools are sensitive to measuring change over time in response to a parenting intervention. The ICAST-Trial should have utility for evaluating the effectiveness of child abuse prevention efforts in similar socioeconomic contexts. Further research is needed to replicate these findings and examine cultural appropriateness, barriers for disclosure, and willingness to engage in child abuse research.